Autonomous Learning Material with YouTube: Case Study for Intensive Reading Course - Estika Satriani; Sri Wahyuni; Fauzul Etfita; Arimuliani Ahmad; Safriani Novitri (AL-ISHLAH: Jurnal Pendidikan, 2023)
The education paradigm has now changed from teacher-centred to student-centred, and media technology has become a current issue that needs to be interested. The objective of the present study is to investigate the utilization of YouTube media as a learning material for teaching Intensive Reading skills, as well as to determine the impact on students' learning attitudes. YouTube is used to acquire new knowledge and information and help complete the learning material, particularly in delivering technical matters. Besides, YouTube also provides a variety wide range of aspects with unlimited content. Thus, It can cultivate students’ autonomous learning capability. Students who are capable of autonomous learning can set their goals, create a study plan, choose skills and methods to be used, monitor their acquisition, and evaluate what they have learned.  This study offered a case studies research design. The case study is based on autonomous learning used in this study. Autonomous learning is an innovative concept that adheres to the advantages of online teaching-learning using YouTube to deliver learning material media. The questionnaire was distributed to 78 students involved in the intensive reading classes to obtain the data. A statistical assessment of the analysis data shows that autonomous learning of intensive reading classes using YouTube positively impacts students' learning attitudes. In other wordss, YouTube application is a learning alternative that allows students to manage the learning process through independence, self-exploration and freedom of learning to achieve optimal learning results.